Optimization of Self-Regulated Learning in the Development of Professional Pdf Flip E-modules in the Implementation of Post-Covid-19 Pandemic Learning in Elementary Schools of Magetan Regency - Amanda Senja Karunia; Sardulo Gembong; Anang Lilik Gunarso (Universitas PGRI Semarang, 2023)
Learning design is the main thing that can support the learning outcomes of students. There needs to be effort in optimizing, especially on the implications of Self Regulated Learning. This effort is expected to be able to coordinate the various abilities of students by increasing learning characteristics. Self Regulated Learning is a learning characteristic that requires students to be responsible for themselves in active learning to improve their learning achievement. Based on the results of research conducted at various levels of education, it was found that the use of Self-regulated Learning has a significant contribution to learning and improves student learning achievement. Therefore it is necessary for us to have broad insight in understanding the psychology of learning and be able to condition it through constructive and meaningful learning designs. Educators are expected to be more observant in understanding the characteristics of students' abilities so that they are more flexible and open.